EKSPLORASI KEBIJAKAN MAKAN BERGIZI GRATIS (MBG) PEMERINTAHAN PRABOWO-GIBRAN DI KEPULAUAN BELITUNG: TANTANGAN DAN SOLUSI DI SEKOLAH DASAR - Harianto Harianto; Hidayati Hidayati (STKIP Pesisir Selatan, 2026)
The Free Nutritious Meals Program is one of the national strategic policies aimed at improving the nutritional quality of children and students as a foundation for human resource development toward Indonesia Emas 2045. This study aims to explore the MBG policy in elementary schools, identify challenges and solutions in its implementation, so that the program can run effectively and sustainably. This study uses a qualitative approach with an exploratory descriptive-analytical method. Data were collected through participant observation, in-depth interviews, questionnaires, and document analysis, involving school principals, teachers, and students at five elementary schools that have implemented or are currently piloting the MBG program. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, data presentation, and drawing conclusions, supplemented by data validity testing. The research results indicate that the MBG program received a positive response from schools because it was deemed relevant to students’ needs and capable of improving student attendance and social interaction. However, program implementation still faces various challenges, such as logistical constraints, the absence of uniform nutritional standards, a shortage of specialized management staff, weak cross-sectoral coordination, limited local funding, and issues regarding the cleanliness of MBG kitchens.